Angel in Aisle 3 : the True Story of a Mysterious Vagrant, a Convicted Bank Executive, and the Unlikely Friendship That Saved Both Their Lives - West, Kevin (Kevin Ray); Edwards, Frederick (New York : Howard Books, an imprint of Simon & Schuster, Inc., 2015)
"When Kevin West resigned from his job as vice president of a bank in 1998 after making fraudulent loans, he spent the time before his trial managing a family-owned, small grocery store in Ironton, Ohio ... It was at his lowest moment that Kevin called out to a power beyond himself for help, and God answered his prayer in the form of an elderly vagrant in a soiled shirt and tattered pants named Don. When Don saw Kevin's open Bible on the counter next to the register, the untidy, long-haired indigent took the opportunity to share Bible wisdom and life-giving truths that changed Kevin's life"--Provided by publisher.
Keywords: West, Kevin; Bible -- Study and teaching -- Ohio; Grocers -- Biography -- Ohio; Tramps -- Biography -- Ohio; Bankers -- Biography -- Ohio; First-time offenders -- Biography -- Ohio; friendship; Redemption; Christian biography -- Ohio; Ironton (Ohio) -- Biography